Pemberdayaan Tokoh Masyarakat dan Institusi Lokal untuk Mencegah Generasi Milenial Menyalahgunakan Narkoba - Dwiyanti Hanandini; Indraddin Indraddin; Wahyu Pramono; Nini Anggraini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
In order to be able to play a role in preventing and overcoming drug abuse, all community leaders and local social institutions need to be empowered. The purpose of this service activity was to understand the management of Community Representative Institutions, Kerapatan Adat Nagari, Bundo Kanduang, Youth Organizations, and Nagari officials in identifying signs of children entangled in drug abuse and empowering them to prevent and overcome drug abuse. The method used to carry out this activity was counselling and Focus Group Discussion (FGD). This activity involved the Nagari Duo Koto apparatus, Tanjung Raya District, Agam Regency. Service activities have been running smoothly, concluding that efforts to prevent drug abuse are very appropriate if done with an approach from local institutions, especially Nagari, to invite the younger generation to have awareness together to stay away from drugs. The team of community service recommended regularly holding outreach events about drugs' effects to attract all parties' attention. So that drug problems can be anticipated before a case occurs in the Nagari.